KONDISI FISIK PEMAIN SEPAKBOLA KLUB ASYABAAB DI KABUPATEN SIDOARJO - SETIAWAN, DENI (Jurnal Kesehatan Olahraga, 2014)
THE PHYSICAL CONDITION OF FOOTBALL PLAYER ONASYABAB CLUB AT SIDOARJO DISTRICTDENI SETIAWANABSTRACTPhysical condition is a whole unit from components that cannot be separatedoff hand, whether the improvement or the maintenance. Problem that proposed inthis research is how the physical condition of football player on ASYABAABclub at Sidoarjo District.Population in this research is the football player onASYABAAB club at Sidoarjo District that amounted of 20 athletes. Researchvariable applying test item concerning physical condition of football player onASYABAAB club at Sidoarjo District. The execution of research using 4 typestest series namely MFT, 40 meter run, shuttle run, and ??jumping rope?? 45 cmmodification. Data analysis that applied in this research applies descriptivepercentage.From the result of test series show that physical ability can obtainedthat MFT belong to moderate category as big as 75%, run test 40 meter belong tomoderate category as big as 40%, shuttle run belong to good category as big as45%, and jumping rope 45 cm modification belong to moderate category as big as55%. So the physical condition of football player on ASYABAAB club atSidoarjo District belongs to moderate category as big as.The conclusion from alltest in this research is the physical condition of football player on ASYABAABclub at Sidoarjo District belongs to moderate category. Those physicaldevelopments still have not running well. The suggestion is to make athletes havetheir own motivation to train their physic based on their need.Keywords : Physical Condition, Football